Hyperspectral imaging for detecting counterfeit currency and forensic applications - Hazim Ismail (2017)
Technology is ever-improving with time. This includes the technology to create copies of currencies using printers and copying machines. With that, the printing and production of inauthentic documents become increasingly sophisticated. Hence, it may prove to be ineffective to detect counterfeit currencies using simple methods such as assessing for watermarks on the currency under visible light. Thus, improvements to the method of detecting counterfeit currencies will also have to improve to keep up with the criminal act. Hyperspectral imaging can be utilised to combat counterfeit currencies. It is one of the latest imaging technology that can detect even the slightest difference within a specimen that cannot be seen through the naked eye. Hyperspectral imaging is one of the most recent appearance in imaging innovation, giving the possibility for research that may be inaccessible to panchromatic imagers. The usefulness of hyperspectral imaging lies in its capability to identify, quantify (measure) and map chemical, physical and biological properties in each pixel of a scanned specimen [1]. This expanded utility comes at the cost of massively expanded information. To have the widest scope of utilisations, extraction of the data obtained must happen progressively. Creating and exploiting 3D datacube of hyperspectral information at video rates may prove to be useful through utilisation of an imager and a capable processor within a framework. However, there may be issues in the scanning procedures when large specimens are used since information rates are scaled by the quantity of spectral planes in the cube. Research shows that hyperspectral imaging can detect even the slightest difference in the spectral intensity of any given wavelengths between the same currencies with given region of interest(s). A spatial scanning pushbroom hyperspectral imaging (HSI) system which incorporates a video camera as well as methods and formulas used for calibration and electronic hardware interface were used to collect data and make analysis. The techniques and system used can hence be extended to currency imaging applications as a form of security and counterfeit detection measures.